Searches for gamma-ray lines and "pure WIMP" spectra from dark matter annihilations in dwarf galaxies with H.E.S.S - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; King, Johannes; Mohamed, Mahmoud; Quirrenbach, Andreas; Schwemmer, Stephanie; Wagner, Stefan (Arxiv, 2018)
Dwarf spheroidal galaxies are among the most promising targets for detecting signals of Dark Matter (DM) annihilations. The H.E.S.S. experiment has observed five of these systems for a total of about 130 hours. The data are re-analyzed here, and, in the absence of any detected signals, are interpreted in terms of limits on the DM annihilation cross section. Two scenarios are considered: i) DM annihilation into mono-energetic gamma-rays and ii) DM in the form of pure WIMP multiplets that, annihilating into all electroweak bosons, produce a distinctive gamma-ray spectral shape with a high-energy peak at the DM mass and a lower-energy continuum. For case i), upper limits at 95% confidence level of about $\langle σ v \rangle \lesssim 3 × 10^{-25}$ cm$^3$ s$^{-1}$ are obtained in the mass range of 400 GeV to 1 TeV. For case ii), the full spectral shape of the models is used and several excluded regions are identified, but the thermal masses of the candidates are not robustly ruled out.